Data variability in rats depending on housing and breeding conditions. Acceptability criteria for biological test systems - A. E. Katelnikova; M. A. Akimova; M. N. Makarova; V. G. Makarov; M. A. Kovaleva; E. A. Shamray; A. Yu. Pereboeva; A. S. Ivkina; D. Yu. Ivkin (Translational Medicine, 2026)
Background. The reliability and reproducibility of preclinical in vivo studies significantly depend on the quality of laboratory animals. Objective. To compare the variability of clinical laboratory and behavioral parameters, as well as the level of microbiological control, in rats obtained from four breeding facilities located in the Russian Federation. Materials and Methods. This paper presents coefficient of variation (CV %) values for complete blood count parameters, biochemical analysis parameters (alanine aminotransferase, aspartate aminotransferase (AST), creatinine, lactate dehydrogenase (LDH), total protein, urea), and hemostasis system parameters (activated partial thromboplastin time and prothrombin time), respiratory rate, and behavioral test parameters (number of rearings against the walls and number of squares visited). The study included 4 groups of 10 males and 10 females each. Results. Based on the data analysis, elevated leukocyte levels were detected in the blood of animals without SPF status; in group 1, rats showed deviations outside the reference intervals for creatinine (20 % higher in males and 7 % higher in females), urea (20 % higher in males and 12 % higher in females), and AST. The coefficient of variation for most parameters was below 20 %, indicating satisfactory homogeneity. High interindividual variability (CV > 20–30 %) was observed only for lactate dehydrogenase (LDH) and behavioral tests. A sex difference was observed: in males, the CV values for leukocyte count and differential leukocyte count ranged from 10 % to 20 %, whereas in females the CV exceeded 20 % in all groups. Respiratory rate and hemostasis parameters showed low biological variability in all groups. Conclusion. The variability of the studied parameters was not influenced by the source of the animals; rather, the method used to analyze the parameter was significant. An attempt was made to define acceptability criteria for variability of major vital parameters in biological test systems. For example, variability with CV < 5 % can be regarded as “too” low (high data homogeneity); CV < 10 % corresponds to low variability (homogeneous data); CV from 10 to 20 % indicates satisfactory variability (data homogeneity acceptable for most parameters); CV from 20 to 30 % reflects moderate variability (data with considerable scatter typical for biological test systems); and CV > 30 % indicates high variability (heterogeneous dataset).